Dynamics of offshore structures - Wilson, James F. 1933-2019 (J. Wiley, 2003)
Using the latest advances in theory and practice, Dynamics of Offshore Structures, Second Edition is extensively revised to cover all aspects of the physical forces, structural modeling, and mathematical methods necessary to effectively analyze the dynamic behavior of offshore structures. Both closed-form solutions and the Mathematica® software package are used in many of the up-to-date example problems to compute the deterministic and stochastic structural responses for such offshore structures as buoys; moored ships; and fixed-bottom, cable-stayed, and gravity-type platforms.